2020
DOI: 10.3390/ijerph17134851
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance Vector Patterns Changes in Response to Swimming Training: An Ecological Approach

Abstract: Background and aim: Monitoring bioelectric phase angle (PhA) provides important information on the health and the condition of the athlete. Together with the vector length, PhA constitutes the bioimpedance vector analysis (BIVA) patterns, and their joint interpretation exceeds the limits of the evaluation of the PhA alone. The present investigation aimed to monitor changes in the BIVA patterns during a training macrocycle in swimmers, trying to ascertain if these parameters are sensitive to training lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Indeed, PhA is positively associated with the ICW/ECW ratio in athletes [ 18 , 24 ]. Bioelectric data reflect the content of body fluids and the cellular health of the athlete and during the season, which change in response to training load and physical condition over the season [ 25 ]. In fact, the new tolerance ellipses proposed in this study differ significantly from those generated in the study by Levi Micheli et al [ 14 ], in which bioimpedance measurements were collected in the first half of the competitive period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PhA is positively associated with the ICW/ECW ratio in athletes [ 18 , 24 ]. Bioelectric data reflect the content of body fluids and the cellular health of the athlete and during the season, which change in response to training load and physical condition over the season [ 25 ]. In fact, the new tolerance ellipses proposed in this study differ significantly from those generated in the study by Levi Micheli et al [ 14 ], in which bioimpedance measurements were collected in the first half of the competitive period.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was shown how the interpretation of the vector position in the R-Xc graph overcomes the limits linked to the interpretation of the PhA alone. In this regard, Reis et al [ 35 ] recently showed that the bioimpedance vector position varied in response to changes in the macrocycle training load in swimmers of both sexes. The authors identified an accumulation of fluids and, therefore, a shortening of the vector following a first phase characterized by a high training load, and then a subsequent shift of the vector position to the left side as a result of muscle adaptations that occurred after a recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…This is a simple assessment that can be used in multiple settings, before regular practice, at home, or while travelling. Additionally, hydration assessment can be of use when assessing body composition such as bioimpedance measurements [ 26 , 27 ], or when performing exercise testing [ 28 ] allowing for a better standardization of measurements. Despite the small significant difference in reporting Uc, no real practical difference exists between the two validated Uc scales when looking at the total number of correctly classified urine samples (up to 77%).…”
Section: Discussionmentioning
confidence: 99%